Quercetin nanoparticles attenuates scopolamine induced spatial memory deficits and pathological damages in rats - Suresh Palle; Prasad Neerati (Faculty of Pharmacy, Cairo University, 2017)
Quercetin is a well-known flavonoid, has low bioavailability. Quercetin nanoparticles (NQC) enhance its bioavailability. NQC were not explored for their potential therapeutic activities in Alzheimer's disease (AD). Hence, the present study was performed to evaluate the protective effect of NQC in comparison to free quercetin against scopolamine induced spatial memory impairments. NQC prepared by anti solvent precipitation method. Quercetin, NQC (30 mg/kg p.o.) and rivastigmine (2 mg/kg i.p.) as a reference drug were administered for 8 consecutive days. At the end of the treatment period memory impairments were induced by a single injection of scopolamine (20 mg/kg; i.p.). Conditioned avoidance and rectangular-maze tests were conducted 30 min thereafter then rats were sacrificed and brain homogenates were used for the estimation of glutathione (GSH), catalase and malondialdehyde (MDA) contents together with acetyl cholinesterase (AchE) activity. In addition, histopathologic studies were also performed. The size of NQC was observed below 300 nm. NQC significantly reduced the transfer latency and conditioned avoidance response compared to scopolamine treated group (p < 0.05). Pretreatment with NQC showed a significant (p < 0.05) decrease in MDA, AchE levels and increase in brain catalase and GSH levels to be similar to that observed in the rivastigmine group. In all the behavioral, biochemical and histological experiments, the rats treated with NQC showed additional distinguished results compared to quercetin group indicating that a preventive strategy against the progression of AD. This approach of quercetin nanoparticles provides the potential therapeutic application in human neurodegenerative disease in future.